Mobile Forensic of Vaccine Hoaxes on Signal Messenger using DFRWS Framework - Imam Riadi; Herman Herman; Nur Hamida Siregar (Universitas Bumigora, 2022)
The COVID-19 pandemic is one of the factors that has increased the use of social media. One of the negative impacts of using social media is the occurrence of cybercrime. The possibility of cybercrime can also happen on one of the social media platforms, such as the Signal Messenger application. In the investigation process, law enforcement needs mobile forensic methods and appropriate forensic tools so that the digital evidence found on the perpetrator's smartphone can be accepted by the court. This research aims to get digital evidence from cases of spreading the COVID-19 vaccine hoaxes. The method used in this research is a mobile forensics method based on the Digital Forensic Research Workshop (DFRWS) framework. The DFRWS framework consists of identification, preservation, collection, examination, analysis, and preservation. The results showed that the MOBILedit tool could reveal digital evidence in the form of application information and contact information with a performance value of 22.22%. Meanwhile, Magnet AXIOM cannot reveal digital evidence at all. The research results were obtained following the expected research objectives.